Variabilidad espacial del fósforo y su relación con las avenidas y estiajes de las cuencas hidrográficas del Nanay, Chillón-Rímac-Lurín y Azángaro - Vasquez Villa, Flavio (2023)
The present investigation was carried out to estimate the degree of vulnerability to eutrophication by phosphorus in surface waters of the basins of the Rímac, Lurín and Chillón rivers of the Pacific basin, Nanay river of the Atlantic basin and the Azángaro river of the Titicaca basin. The data was collected from the National Water Resources Information System (SNIRH), the National Water Authority (ANA) and the National Meteorology and Hydrology Service (SENAMHI). The Kruskall-Wallis non-parametric test and a Post Hoc analysis between pairs, with Bonferroni adjustment, were used to determine which of the sample groups are significant in terms of vulnerability. For the prediction analyzes of the time series of the variations of the total phosphorus concentration in the basins, the Holt-Winters mathematical model with exponential smoothing was used. It was found, according to the Holt Winter prediction analysis, that for the dry season in Nanay, slight increases in total phosphorus concentration levels are expected, which exceed the LMP and maintain a slight increase for the next few years. While in avenues the concentration levels are below the LMP and with a decreasing trend in the coming years. In the Rímac river, during the dry season and flood, concentration levels are expected to exceed the LMP in the coming years. In the Lurín river, for the dry season and flood, it foresees concentration levels that greatly exceed the LMP in the coming years. In the Chillón river, for dry seasons and floods, concentration levels are expected to exceed the LMP for the coming years, but in flood times the concentration levels have a decreasing trend. On the other hand, in the Azángaro river, the analysis foresees that the concentration levels for the dry season and flood season are similar, do not exceed the LMP and that they have a decreasing trend line for the coming years. There is statistical significance (p<0.05) between the levels of spatial vulnerability to eutrophication (phosphorus concentrations) between the hydrographic basins located on the Pacific, Atlantic and Titicaca slopes, evidencing the significance in the most significant paired basins of Nanay (Atlantic). - Chillón (Pacific), Nanay (Atlantic)-Lurín (Pacific), Azángaro (Titicaca)-Chillón (Pacific) and Azángaro (Titicaca)-Lurín (Pacific), therefore the alternative hypothesis is accepted and the null hypothesis is rejected.